PEMBUATAN DAN KARAKTERISASI ELEKTRODA KARBON AKTIF DENGAN KARBONISASI DAN AKTIVASI BERTINGKAT MENGGUNAKAN GAS CO2 DAN UAP AIR - Rakhmawati Farma., Yusriwandi, Erman Taer,; Taer, Erman (Edu Research, 2017)
Has been conducted a research to produce cell supercapacitor electrodes of activated carbon (AC) which were prepared using rubber wood sawdust (SGKK). KA electrode is made via carbonization and activation method integrated using CO2 and water vapor for 4 hours. N2 flow is maintained from room temperature to a temperature of 600 0C, followed by CO2 to a temperature of 900 0C for 2 hours, water vapor flow continued for 2 hours at a temperature of 900 0C. Crystallite structure is reviewed samples using X-Ray Diffraction (XRD). Methods Scanning Electron Microscopy (SEM) was used to analyze the surface morphology. While the composition of the content chemical elements the samples were analyzed using Energy Dispersive X-ray (EDX). Electrochemical properties of samples were tested using the method Cyclic Voltammetry (CV). Overall characterization of physical properties indicates that the sample is a carbon material with a carbon content of 90%. Electrochemical test proved that the integrated activation method can produce aÂ  electrode with excellent performance with a specific capacitance value of 72 F/g.